Brand Image Of Toyota Sparepart At Lampung Service Workshop As Customer Choice - Fauzi Efendi; Vethy Octaviani; Sapta Sari (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
The use of spare parts  increases every year. The spare part brand recommended by Lampung Service Workshopprovides a workshop warranty. The workshop provides a guarantee on the recommended spare parts on the grounds that the workshop does not want to experience loss of service or material, this is also related to the image of Lampung Service Workshop if the workshop has dared to guarantee a spare part will give a positive image. This study aims to describe the Brand Image of Toyota Spare Parts  at  Lampung  Service  Workshop as  Customer  Choice.  This  research  uses qualitative research with data collection techniques of observation, interviews and documentation and research informants 5 people who are workshop owners, mechanics and consumers. The theoretical basis used in this research is the Elements of Brand Image according to Kerby in Sandy (2010; 22)  which include Resilience, Conformity, Accuracy, and Connotation. The results showed that: first,  the resilience (Tenacity).  Relating  to  the  quality  and  brand  image  of  the product  itself.  the durability of  Toyota products  is superior to other brands, only in terms of price, Toyota is slightly more expensive than other products, customers of Lampung service workshops  know  the durability of  Toyota products  based on  the  user's personal experience and explanations from  the workshop itself. Second, the conformity of the Toyota  brand  with  consumer  needs  and  expectations.  The  suitability  felt   by consumers varies, ranging from  the suitability of price with quality, conformity with the delivery of the workshop owner, and conformity with the durability of the product itself. Third, thoroughness: Toyota brand accurately and consistently in accordance with the quality and information conveyed, in addition to the Toyota brand the price offered  in every place  must be consistent or the same.  There are no similarities between the Toyota brand and other brands, so Toyota can be said to be more chosen by customers  than  other  brands. Fourth,  connotation: Products  with  the  Toyota brand  are  more  in  demand  than  other  brand products,  this  is  because  Toyota products  are considered to be more able to meet the needs of consumers!customers because  in terms of prices  they are  more affordable, product  durability  is more durable, easy to obtain and environmentallyfriendly..